Multisensory integration with a head-mounted display ackground visual motion and sound motion - Harrison, WIlliam J (Human Factors: The Journal of the Human Factors and Ergonomics Society)
The aim of this study was to assess how background visual motion and the relative movement of sound affect a head-mounted display wearer's performance at a task requiring integration of auditory and visual information.